Base‐catalyzed Effective C2‐Amidation of Azolium Salts Using Isocyanates under Mild Conditions. Issue 7 (27th February 2023) - Bauri, Somnath; Ramachandran, Arya; Rit, Arnab
Abstract: An unprecedented base‐catalyzed hydroarylation of isocyanates with azolium salts was developed, which follows a simple reaction pathway and provided facile access to diverse C2‐amidated azolium salts under mild conditions. Importantly, this methodology can also be applied for the successive C2‐amidation of a bisimidazolium salt with two different isocyanates to provide the corresponding unsymmetrically substituted bisamide derivatives. Notably, the obtained amidated salts can also serve as a prominent carbene surrogate for the synthesis of metal‐NHC complexes. Abstract : An efficient base‐catalyzed hydroarylation of isocyanates with azolium salts was developed, which provided facile access to a diverse family of C2‐amidated azolium salts under mild conditions.